Energy benchmarking management for beer and beverage industry in Vietnam - Minh Nguyen Dat; Kien Duon Trung; Hoang Truong Huy (Zielona Góra: Faculty of Economics and Management Press)
The purpose of this paper is to introduce basic principles of benchmarking and explain the methodology to set the specific energy consumption (SEC) target for the beer and beverage industry in Vietnam to evaluate performance, support decisions, and energy efficiency (EE) improvement. Energy benchmarking management method is used to assess EE performance.
Keywords: energy efficiency; energy benchmarking; specific energy consumption; beer industry; beverage industry; Vietnam; efektywność energetyczna; benchmarking; zużycie energii; przemysł piwny; Wietnam